Tradisi Nyaran Ojen Di Kecamatan Tanjung Pura Dalam Perspektif MUI Langkat - Arina Husna (Journal Smart Law, 2023)
The Javanese people are a group that still carries out the rain handler service tradition in carrying out events and celebrations or what is also called nyaran ojen. People think that holding a wedding or celebration will bring bad luck because of the rain. The people believe that the presence of the rain handler can control the rain. What the villagers did and believed was an act of deviation from the true Islamic faith. Therefore, it is necessary to conduct research related to the nyaran ojen tradition, especially what happened in Pematang Serai Village, Tanjung Pura District. This study aims to find out the tradition of nyaran ojen in marriage in the village, along with the reasons why people still practice this tradition, as well as to find out the opinion of the Langkat MUI regarding this tradition. The type of45research used is field research with a qualitative approach. Data were collected using interview and observation techniques, with primary data sourced from interviews with rain handler service users and the Langkat MUI, supported by secondary data sourced from relevant reading materials. Data analysis is done by organizing data, synthesizing, compiling into patterns, and making conclusions. The results of his research are: first, the handler of the rain is an expert in moving rain by carrying out a special ritual and using certain materials. This rain handler is needed in events or celebrations; secondly, the reason why people use the rain handler is because the rain handler is a ritual request so that there is no rain during the celebration; third, the Langkat MUI is of the opinion that the rain charmer tradition deviates from Islamic aqeedah, because the procedure for its implementation is categorized as an act of shirk, namely asking for help from other than Allah.